Ethnic stereotypes and preferences on poverty assistance - Ágnes Horváth; Béla Janky (Kiel Institute for the World Economy (IfW), 2014)
The authors introduce a simple model of public preferences on poverty assistance. Their focus is on the roles played by the socioeconomic status of a potential welfare recipient and the stereotypes about his/her ethnic group in shaping taxpayers' preferences on appropriate assistance. The model assumes that status not only informs one about the recipient's material needs but also sends noisy signals about his/her 'deservingness'. Ethnic stereotypes about work ethic, in turn, help to process those noisy signals. The authors show that the influence of stereotypes on welfare preferences tends to diminish as the status of a potential recipient approaches middle-class standards. Their model points to the potential of institutional and media framing of poverty assistance in the ethnicization of welfare preferences.
Keywords: H8; I3; 330; Poverty assistance; welfare preferences; social preferences; deservingness; stereotypes